2015
DOI: 10.3390/ijerph120809562
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Early Initiation of Breastfeeding in Western Nepal

Abstract: The initiation of breastfeeding within one hour of birth has numerous nutritional and immunological benefits and has been found to reduce neonatal mortality. This community-based prospective cohort study aimed to report the rate of, and factors associated with, early initiation of breastfeeding in Western Nepal. The rate of early initiation of breastfeeding was reported, and associations between early initiation and independent variables were tested by Chi-square test, followed by multiple logistic regression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
98
6
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(134 citation statements)
references
References 27 publications
23
98
6
7
Order By: Relevance
“…These results have been shown elsewhere: a recent meta-analysis indicated that early initiation of breastfeeding is low globally [30], and an additional systematic review identified prelacteal feeding as a major barrier to early initiation of breastfeeding in South Asia [31]. Other studies have shown a delay in breastfeeding associated with prelacteal feeding in Ethiopia [23, 32] and western Nepal [33]. …”
Section: Discussionsupporting
confidence: 57%
“…These results have been shown elsewhere: a recent meta-analysis indicated that early initiation of breastfeeding is low globally [30], and an additional systematic review identified prelacteal feeding as a major barrier to early initiation of breastfeeding in South Asia [31]. Other studies have shown a delay in breastfeeding associated with prelacteal feeding in Ethiopia [23, 32] and western Nepal [33]. …”
Section: Discussionsupporting
confidence: 57%
“…This district is located in the south-western plain areas (Terai) of Nepal bordering India in the south. The methodology of this study has been described previously [31, 32] but briefly 735 mother-infant pairs (rural 378, urban 357) were randomly recruited from 15 rural and 12 urban locations. Mothers were recruited from their communities within 30 days of giving birth and followed up during the fourth (90–120 days) and sixth months (150–180 days) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1 There are very few studies examining the role of awareness of world health organization's breastfeeding recommendation in determining mothers breastfeeding decisions and practice. 2 As a result, the impact of promoting the recommendation on rates of breastfeeding is less clear.…”
Section: Introductionmentioning
confidence: 99%